PEMENTASAN MUSIK ANSAMBEL PADA MASA PANDEMI COVID-19 SMP NEGERI 5 LHOKSEUMAWE - Julia Julia (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The title of this research is the musical ensemble performance of SMP Negeri 5 Lhokseumawe for the 2020/2021 academic year. Raising the problem of how the implementation of ensemble music performance activities at SMP Negeri 5 Lhokseumawe and the factors that influence these activities. This study aims to describe how ensemble music staging activities during the covid-19 pandemic and describe the problem solving used to overcome these problems by applying the demonstration method. This type of research is Classroom Action Research with stages of planning, action, observation and reflection. This study applies three cycles, each cycle students' abilities have increased. In the first cycle, the average ability to play music was 44.4%, in the second cycle there was an increase of 66.6%, then in the third cycle there was a significant change to 94.6%. Data collection in this study was obtained by means of observation and documentation. From the results of this study, it was concluded that the demonstration method could improve the ability to play ensemble music during the Covid-19 Pandemic in class IX. 5 Shift A SMP Negeri 5 Lhokallwe. It is suggested that the demonstration method can be used or utilized in learning the art of music to improve the ability to play ensemble music in learning arts and culture, because it will provide a meaningful experience for students and be beneficial for all.